Investigation of a novel biocide material for biocorrosion in simulated seawater: A case study on Tinospora cordifolia extract - Ahmad Royani; Muhammad Hanafi; Victor Sunday Aigbodion; Muhammad Eka Prastya; Chandrabhan Verma; Nabisab Mujawar Mubarak; Akram Alfantazi; Azwar Manaf (Case Studies in Chemical and Environmental Engineering)
This case report investigates the preventive effect of Tinospora cordifolia extract on biocorrosion induced by Pseudomonas aeruginosa on mild steel API 5L in the simulated seawater medium. Electrochemical techniques, spectroscopic techniques, and surface analysis were employed to investigate biocide performance and corrosion behavior. P. aeruginosa has been shown to enhance iron dissolution in seawater medium. These findings point to the role of P. aeruginosa bacteria in forming differential oxygen, which causes corrosion. Morphology results from atomic Fourier microscopy (AFM) highlight the presence of P. aeruginosa in biotic environments, where the surface is rougher than in abiotic conditions. On the other hand, adding T. cordifolia to the biotic medium resulted in a smoother and more homogeneous surface without any significant deterioration. Electrochemical findings reveal that adding 300 mg L−1 of T. cordifolia extract prevents the microbiologically influenced corrosion (MIC) of steel API 5L, with an optimum effectiveness value of 74.50 % after 21 days of incubation. This protective effect is caused by forming a more compact iron oxide surface layer and the adsorption of phenolic active compounds such as Moupinamide and others on the surface of mild steel API 5L, as detected by liquid chromatography-mass/spectrometry-mass spectrometry (LCMS-MS), Fourier-transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FE-SEM) techniques.